A comparison of changes in river runoff from multiple global and catchment-scale hydrological models under global warming scenarios of 1°C, 2°C and 3°C - Gosling, Simon; Zaherpour, Jamal; Mount, Nick J.; Hattermann, Fred; Dankers, Rutger; Arheimer, Berit; Breuer, Lutz; Ding, Jie; Haddeland, Ingjerd; Kumar, Rohini; Kundu, Dipangkar; Liu, Junguo; et al. (Springer Verlag, 2016)
We present one of the first climate change impact assessments on river runoff that utilises an ensemble of global hydrological models (Glob-HMs) and an ensemble of catchment-scale hydrological models (Cat-HMs), across multiple catchments: the upper Amazon, Darling, Ganges, Lena, upper Mississippi, upper Niger, Rhine and Tagus. Relative changes in simulated mean annual runoff (MAR) and four indicators of high and low extreme flows are compared between the two ensembles. The ensemble median values of changes in runoff with three different scenarios of global-mean warming (1°C, 2°C and 3°C above pre-industrial levels) are generally similar between the two ensembles, although the ensemble spread is often larger for the Glob-HM ensemble. In addition the ensemble spread is normally larger than the difference between the two ensemble medians. Whilst we find compelling evidence for projected runoff changes for the Rhine (decrease), Tagus (decrease) and Lena (increase) with global warming, the sign and magnitude of change for the other catchments is unclear. Our model results highlight that for these three catchments in particular, global climate change mitigation, which limits global-mean temperature rise to below 2°C above pre-industrial levels, could avoid some of the hydrological hazards that could be seen with higher magnitudes of global warming.